Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/iub.1695
|View full text |Cite
|
Sign up to set email alerts
|

TIMAP, the versatile protein phosphatase 1 regulator in endothelial cells

Abstract: Transforming growth factor (TGF)-β inhibited membrane associated protein, TIMAP, is the member of the myosin phosphatase targeting protein (MYPT) family of protein phosphatase 1 (PP1) regulatory subunits. The N-terminal part of TIMAP has a typical MYPT family structure with a sequence element called MyPhone (myosin phosphatase N-terminal element), a putative bipartite nuclear localization signal, a PP1 catalytic subunit binding motif, and five ankyrin repeats. The C-terminal half of TIMAP is intrinsically diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 86 publications
0
21
0
Order By: Relevance
“…Although our experiments indicate that TIMAP/PP1cβ inhibits myosin phosphatase activity in ECs, it is still possible that TIMAP/PP1cβ targets other substrates; for instance, the ERM proteins moesin and merlin (17, 34, 56). In this regard, a previous study found that TIMAP WT overexpression did not alter baseline ERM phosphorylation (17), similar to findings in this study (Fig.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Although our experiments indicate that TIMAP/PP1cβ inhibits myosin phosphatase activity in ECs, it is still possible that TIMAP/PP1cβ targets other substrates; for instance, the ERM proteins moesin and merlin (17, 34, 56). In this regard, a previous study found that TIMAP WT overexpression did not alter baseline ERM phosphorylation (17), similar to findings in this study (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…We investigated whether TIMAP/PP1cβ acts as a functional myosin phosphatase in living ECs because TIMAP is an EC-predominant MYPT1 family member (22) that supports myosin-dependent EC processes like angiogenesis (30) and maintenance of pulmonary EC barrier integrity (34). We found that, although TIMAP partially colocalizes and directly interacts with MLC2, it inhibits MLC2 dephosphorylation in ECs by competing for PP1cβ with MYPT1, leading to MYPT1 degradation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the interaction between muscular layer and the vessel, vascular biology and contractility may play an additional role. CALCB , which plays a role in mesenteric vascular smooth muscle function50 and protein phosphatase 1 regulatory subunit 16B ( PPP1R16B ), which regulates endothelial cell function51 may provide a potential mechanistic basis for altered vascular biology at these entry points.…”
Section: Discussionmentioning
confidence: 99%
“…70 Also reported to be highly methylated 71 in CRC (relative to normal) is the promoter region of PP1R16B (protein phosphatase 1 regulatory subunit 16B), which codes for a membrane protein that regulates protein phosphatase 1 in endothelial cells. 72 The locus of GDF6 (growth differentiation factor 6), a gene that has a role in vascular stabilization, 73 is also highly methylated 74 in CRC. CLIP4 (CAP-Gly domain-containing linker protein family member 4), whose function is largely unknown, has been reported to be hypermethylated in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%